Desindustrialização no novo padrão de reprodução do capital latino-americano - Dias, Daniel Senna (2021)
After nearly half a century of industrialization, Latin America remains a primary exporter. Many economic theories sought to explain the current situation of economic stagnation with deindustrialization, in our opinion, none of them managed to articulate the main problems experienced by these economies with a more totalizing perspective. According to the Marxist Theory of Dependence, the transformations that took place in the Latin American periphery followed the course of maintaining the dependent condition, which is defined as the situation of subordination between nations in the historically constructed economic sphere. Dependence shapes the economic structures of the periphery within an external and internal dialectic, external changes in the world economy, when internalized, reproduce a unique capitalism. To understand this type of suis generis capitalism, we use a category at an intermediate level of abstraction between the world economy (totalizing) and the Latin American social and economic formations, called the capital reproduction pattern. In contemporary capitalism, fictitious capital takes control of capital accumulation, making everything subordinate to its logic. The pattern of reproduction of Latin American capital, in addition to being primary exporter and specialized, is also a platform for fictitious and financial valuation. In this sense, we defend the hypothesis that there is a symbiotic relationship between financialization with the reprimarization of the export agenda and deindustrialization. We confirm this through an analysis of qualitative data on exports and imports and data on the ongoing deindustrialization in Brazil and, subsequently, an investigation on the balance of payments in Argentina, Brazil and Mexico, especially the financial account. We end with an explanation of the significant increase in public debt, which leads to a loss of policy autonomy. Finally, the configuration of financialized capitalism, together with the unequal and combined integration in the world market between imperialist and dependent countries, shapes a pattern of reproduction of capital whose consequence is the deindustrialization of the periphery.